Isolating the Arabidopsis thaliana genes for de novo purine synthesis by suppression of Escherichia coli mutants. I. 5'-Phosphoribosyl-5-aminoimidazole synthetase. - Senecoff, J F (1993)
We have initiated an investigation of the de novo purine nucleotide biosynthetic pathway in the plant Arabidopsis thaliana. Functional suppression of Escherichia coli auxotrophs allowed the direct isolation of expressed Arabidopsis leaf cDNAs. Using this approach we have successfully suppressed mutants in 4 of the 12 genes in this pathway. One of these cDNA clones, encoding 5'-phosphoribosyl-5-aminoimidazole (AIR) synthetase (PUR5) has been characterized in detail. Analysis of genomic DNA suggests that the Arabidopsis genome contains a single AIR synthetase gene. Analysis of the cDNA sequence and mRNA size suggests that this enzyme activity is encoded by a monofunctional polypeptide, similar to that of bacteria and unlike other eukaryotes. The Arabidopsis AIR synthetase contains a basic hydrophobic transit peptide consistent with transport into chloroplasts. Comparison of both the predicted amino acid and nucleotide sequence from Arabidopsis to those of eight other distant organisms suggests that the plant sequence is more similar to the bacterial sequences than to other eukaryotic sequences. This study provides the groundwork for future investigations into the regulation of de novo purine biosynthesis in plants. Additionally, we have demonstrated that functional suppression of bacterial mutants may provide a useful method for cloning a variety of plant genes.